Programa Orienta : plan de acción tutorial universitaria para estudiantes de primer curso - Rufino Cano González; Ana Paula Pedro (Universidad de La Rioja, 2013)
Valladolid University, through the vice-rectory of Quality and Educational Innovation and probably, the Department of Educational Science in Aveiro University (Portugal), have proposed carrying out a series of specific actions which, in practise, must be specified in a series of Innovative Teaching Plans within the Framework of EEES for the improvement of teaching quality which we can find in this article: a "University Tutorial Plan of Action" through the creation and consolidation of tutorial action groups with first year degree students. The objective is none other than the function of University Tutorials "it includes other aspects relative to the integral development of students while at University". For this reason a group of professors who teach Diploma Qualifications for Primary School Teachers have decided to take on board the proposal and extend it to other colleagues with the intention of designing an intervention programme, with a marked experimental character, and a preliminary fulfilment of a series of formal requirements accompanied by the approval of the Dean's Department of the Faculty of Education and Social Work, the place chosen for the next experimental application.